On greedy codes - Bumanglag, Oscar M., Jr. (Animo Repository, 2015)
One of the special type of Lexicographic code is called the Greedy code (C) wherein all possible vectors in the eld Fn 2 where taken, starting from the zero vector up to the last vector in Fn 2 . This greedy codes are linear with dimension n {u100000} m where m is the index of the B-order of Fn 2 . The parity check matrix for C is H = [g(en) g(e2)g(e1)] where for any 1 i n, ei are the standard unit basis. Also for each vector z in Fn 2 , g(z) is the syndrome of z relative to H. Triangular-greedy codes is one type of greedy code wherein it is generated from the triangular ordered basis. It contains only even weight vectors and for distance exactly equal to 2 the triangular-greedy code is the set of all even weight vectors. In this paper, I discuss the dimension of the triangular greedy-codes of length n and distance d. v